Analisa Kemampuan Analisis Siswa Dalam Menyelesaikan Soal-Soal Fisika Materi Kalor Pada Siswa Kelas X SMA Angkasa Pattimura Ambon Yang Diajarkan Menggunakan Model Contextual Teaching And Learning - Hurulean, Rosalia; Esomar, Ketarina; Kesaulya, Noke; Nirahua, Juliana (Physikos: Journal of Physics and Physics Education, 2022)
This study aims to determine students' analytical skills in solving physics problems using the Contextual Teaching and Learning (CTL) learning model. The type of research is descriptive research. The research data shows that in the initial test the average value of the in itial ability of students is 15,84 seen from the analytical ability of C2 of 38,88%, C3 of 18,75%, C4 of 21,52%, thus the average initial ability of students is classified as a failed qualification. The average value of students' analytical skills during the learning process is 81,01% with the complete category. The final a bility data average value is 81,14, seen from the analytical ability of C2 of 83,33%, C3 of 75%, C4 of 72,54%. Thus, it can be concluded that the CTL learning model can be used to analyze the ability of students to solve problems.